Brome Hay Cost-Return Budget in Central and Eastern Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2009)
This publication compares the income per acre and cost per acre of producing brome hay in central and eastern Kansas.
MF2143_2009_12
Keywords: MF2143; Crops; Economics; MF